Synthesis of 5,6-Dihydro-4H-pyrrolo[1,2-b]pyrazoles and Homologs from 5-Substituted 2-(Alkynyl)tetrazoles via Microwave-Induced Intramolecular Nitrile-Imine–Alkyne 1,3-Dipolar Cycloaddition - Yoneyama, Hiroki; Adachi, Mano; Morita, Aoshi; Nakagawa, Maki; Baba, Miho; Yamawaki, Kanako; Hayama, Noboru; Harusawa, Shinya; Usami, Yoshihide (Synthesis, 2022)
Microwave irradiation of 2-alkynyl-5-(phenyl or alkyl)tetrazoles affords 2-(phenyl or alkyl)-5,6-dihydro-4H-pyrrolo[1,2-b]pyrazoles via intramolecular [3+2] cyclization of nitrile-imine intermediates. In the present method, the use of 5-alkyltetrazoles as the starting materials is more advantageous because of the difficulties associated with conventional photoreactions. From 2-phenylalkynyl-5-methylthio-1H-tetrazoles, the reaction efficiently produces 2-methylthio-3-phenyl-5,6-dihydro-4H-pyrrolo[1,2-b]pyrazoles. The procedure using the methylthio group is applied to the total synthesis of three naturally occurring withasomnines. The method is also extended to the construction of molecules in which bicyclic pyrazoles are fused to six- to eight-membered rings.
Keywords: 2,5-disubstituted tetrazole; 5,6-dihydro-4H-pyrrolo[1,2-b]pyrazole; microwave; nitrile-imine; 1,3-dipolar cycloaddition; withasomnine